An orthographic effect in loanword adaptation (Amherst demo, 2016)
Loanword corpora have been an important tool in studying the relationship between speech perception and native-language phonotactics. Recent work has challenged this use of loanword corpora on methodological grounds, based on the fact that source and possibly loan orthography conditions the adaptation. The present study replicates and extends this finding by using information theory to quantify the relative strength of orthographic effects, in the adaptation of English vowels into Korean. It is found that the orthographic effect is strong for unstressed vowels, but almost unnoticable for stressed vowels. It is proposed that orthography plays a large role in adaptation only when the source form is perceptually compatible with multiple phonological parses in the borrowing language.
Keywords: loanword adaptation; Korean; orthography; information theory